Association of ectatic non-infarct-related artery with 1-month stent thrombosis in patients with ST elevation myocardial infarction. Issue 1163 (17th March 2022) - Zeren, Gönül; Avci, İlhan İlker and Sungur, Mustafa Azmi and Şimşek, Barış and Sungur, Aylin and Yılmaz, Mehmet Fatih and Can, Fatma and Gurkan, Ufuk and Karabay, Can Yücel
Abstract: Background: Ectatic infarct-related artery (IRA) has been shown to be associated with higher thrombus burden, no-reflow, stent thrombosis (ST) and major adverse cardiovascular events in patients with ST-elevation myocardial infarction (STEMI). The effect of ectatic non-IRA on ST without ectatic IRA is not known. We aimed to assess the effect of ectatic non-IRA presence on ST within 1 month after primary percutaneous intervention (pPCI) in patients with STEMI. Methods: A total of 1541 patients with a diagnosis of STEMI and underwent pPCI between 2015 and 2020 were retrospectively included in the study. Patients with and without 1 month ST were compared. Penalised logistic regression method was used to assess the association between ST and candidate predictors due to the risk of overfitting. Results: Median age of the study group was 56.5 (48.7 to 67.2) years. The Synergy between PCI with Taxus and Cardiac Surgery (SYNTAX) score, ectatic non-IRA presence and use of tirofiban were significantly higher in the ST group (18.2±9.9 vs 15.1±9.9, p=0.03; 25% vs 7.2%, p<0.001; 54.2% vs 30.5%, p<0.001; respectively). Significantly higher thrombus aspiration (14.3% vs 6.7%, p=0.03) and lower stent implantation (67.7% vs 84%, p<0.001) rates were observed in ectatic IRA group compared with ectatic non-IRA group. In multivariable analysis, ectatic non-IRA presence was independently associated with 1-month ST (OR 4.01, 95% CI 1.86 to 8.63, p=0.01). Conclusion: Ectatic non-IRA presence without ectatic IRA in patients with STEMI increases the risk of ST within the first month of pPCI.